Analisis Kualitas Pelayanan Di Bandar Udara Abdul Rachman Saleh Kota Malang - Bima Wahyu Ramadhani; Teguh Ariebowo (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Air transportation has an important role in providing transportation services for the transportation of people and goods between one airport and another, which is located connecting one country to another by using airplanes through flight routes (flight routes). The role of the airport as an air transportation infrastructure that continues to grow, is not only a symbol of transportation but also a symbol of the economy. The author raises the title of the thesis about